Treatment of Degenerative Meniscal Tears: Comparison between Conservative Treatment and Arthroscopic Partial Meniscectomy - يوسف علي; يوسف صفوان; بطيخة رامي (Latakia University Journal -Medical Sciences Series, 2020)
Arthroscopic partial meniscectomy is one of the most common orthopaedic procedures specially for degenerative nontraumatic meniscal tears, and its precentage is increasing worldwide. The main objective of the study is to compare results after arthroscpic partial meniscectomy followed by a structured exercise program and treatment with exercise program alone in terms of pain, knee function, sport activities. And to compare our results with recent global studies. The study included patients, wih degenerative meiscal tears admitted to the department of orthopaedic surgery at Tishreen University hospital in year 2019. 49 patients met out inclusion criteria and therefore were included in the study. 27 patients were treated operatively and 22 with conservative treatment. 29/59%/ were males, 20/41%/ were females. The majority of tears were in the posterior horn of the medial meniscus 43 patients /87%/. A detailed post treatment clinical and radiological assessment was performed at 3,6 months. Results were assessed using the international knee documentation committee in terms of symptoms, knee function and sport activities, in addition to pain level and patient satisfaction rate. Results of arthroscopic partial meniscectomy were not superior to conservative treatment. IKDC scores 6 months after treatment were 84.3 for surgery group, 86.6 for physio therapy group. Improvement from base line values were 21.8-19.7 respectively, between group difference 2.1, P-value is 0,006. Therefore physio therapy is considered first line of treatment for degenerative meniscal tears for elderly and middle aged patients.